Case Report: Testicular Torsion in Unilateral Supernumerary Testis - Lu Xiaofei; Zhou Benzhang (Frontiers in Pediatrics, 2022)
Supernumerary testis (SNT), or polyorchidism, is a rare congenital anomaly of the genitourinary tract, described as the presence of more than two testicles. Testicular torsion (TT) in unilateral SNT is extremely rare. We report a case of unilateral SNT in a 16-year-old boy accompanied by TT, which was diagnosed preoperatively based on the outcomes of physical examination and ultrasound and confirmed intraoperatively. We opted for orchiectomy of this SNT because of the long-time hypoperfusion. And as for the normal testis, orchidopexy was performed. His clinical presentation subsided after surgery, and the patient was discharged 3 days later.